Non-isothermal pyrolysis characteristics of giant sensitive plants using thermogravimetric analysis - Wongsiriamnuay T. (2017)
A giant sensitive plant (Mimosa pigra L.) or Mimosa is a fast growing woody weed that poses a major environmental problem in agricultural and wet land areas. It may have potential to be used as a renewable energy source. In this work, thermal behaviour of dried Mimosa was investigated under inert atmosphere in a thermogravimetric analyzer at the heating rates of 10, 30, and 50 °C/min from room temperature to 1000 °C. Pyrolysis kinetic parameters in terms of apparent activation energy and pre-exponential factor were determined. Two stages of major mass loss occurred during the thermal decomposition process, corresponding to degradation of cellulose and hemicellulose between 200-375 °C and decomposition of lignin around 375-700 °C. The weed mainly devolatilized around 200-400 °C, with total volatile yield of about 60%. The char in final residue was about 20%. Mass loss and mass loss rates were strongly affected by heating rate. It was found that an increase in heating rate resulted in a shift of thermograms to higher temperatures. As the heating rates increased, average devolatilization rates were observed to increase while the activation energy decreased. © 2010 Elsevier Ltd. All rights reserved.